Age-dependent nonlinear relationship between hypertension and hippocampal volume in sedentary women with lower educational attainment - Sneha Ravichandran; Poovitha Shruthi Paramashiva; Rajagopal Kadavigere; Hari Prakash Palanisamy; K N Shivashankar; Baskaran Chandrasekaran; M. G. Ramesh Babu; Winniecia Dkhar; Dilip Shettigar; Sathya Sabina Muthu; Suresh Sukumar (Journal of Education and Health Promotion)
BACKGROUND: This study investigated the age-dependent nonlinear relationship between hypertension stages, hippocampal volume, and cognitive performance in sedentary women with lower educational attainment. MATERIALS AND METHODS: Forty-four women (40–60 years) with low education and physical activity levels underwent Magnetic Resonance Imaging brain scans and cognitive tests. Hippocampal volumes were analyzed using CAT12 and SPM12. RESULTS: Age-dependent relationships between systolic blood pressure (SBP) and hippocampal volume were observed. In ages 40–49, higher SBP correlated with more minor left hippocampal volumes (r = -0.5937, P = 0.0046). In ages 50–59, greater SBP is associated with larger hippocampal volumes (left: r = 0.7040, P = 0.0002; right: r = 0.5885, P = 0.0031). Hippocampal measurements accounted for 48.2% and 70.3% of SBP variance in younger and older groups, respectively. Higher SBP correlated with poorer cognitive performance in Flanker (reaction time: χ² = 13.87, P = 0.003; accuracy: χ² = 31.36, P < .001) and N-back tasks (reaction time: χ² = 11.63, P = 0.009; accuracy: χ² = 22.20, P < .001). CONCLUSION: These findings challenge the “lower is better” blood pressure paradigm, especially in older adults, suggesting the need for age-specific hypertension management and brain health preservation strategies. Public health implications include developing tailored interventions considering age, education, and physical activity; implementing age-specific blood pressure guidelines; integrating cognitive screenings into hypertension care; and creating targeted health literacy programs. Future research should establish causality, explore mechanisms, and evaluate personalized strategies for this vulnerable population.